Amphioxus: a peaceful anchovy fillet to illuminate Chordate Evolution (II) - Jordi Garcia-Fernàndez (International Journal of Biological Sciences, 2006)
The genome of the amphioxus is on the horizon. With Linda Holland and Jeremy Gibson-Brown at the forefront, with all the amphioxus community behind, and with the Joint Genome Institute, the amphioxus genome will see the light this year, 2006. Hope that it will reflect the “prototypical” preduplicative genome of vertebrates. It may answer definitively what the human genome did not: Are we vertebrates octaploid? Will it shed light on the novelties that helped non-chordates to be chordates? And more, will amphioxus, with a simpler genome, be developed to a senior “experimental model system”, allowing the testing of molecular functions in a non-duplicated genome background and allowing genetic modification to “recapitulate” evolution? Thanks to an outstanding collaboration between labs, the laboratory culture of amphioxus is underway after years of hard work in the field. 2007 looks promising for amphioxus research.